Hydrogen Fuel Cell used in Vehicles (International Journal of Food and Nutritional Sciences, 2022)
Hydrogen Fuel Cell Cars (FCVs) are similar to electric vehicles (EVs) in that they power their wheels with an electric motor rather than an internal combustion engine. FCVs, on the other hand, create their own power rather than relying on batteries that must be recharged. Exploiting the global potential of renewable energy is now being examined as a means of generating energy utilizing technologies that are both efficient and low-polluting. One of the alternate alternatives for future clean energy systems is hydrogen fuel cell technology. The paper gives a comprehensive, up-to-date examination of fuel cell powered cars, including their working principle, essential components, how they vary from traditional electric vehicles, and their benefits. The study also goes into how hydrogen is refueled and what makes up a hydrogen filling station. In the future new energy generating methods are required in this environment to achieve minimal carbon emissions while also exploiting the potential of renewable energy sources.